2002
DOI: 10.1002/j.2161-1912.2002.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

A Revision of the Multicultural Counseling Awareness Scale

Abstract: This article reports the results of 2 studies designed to test and revise the Multicultural Counseling Awareness Scale (J. G. Ponterotto et al., 1996). Collective results support the 2‐factor extraction (Knowledge and Awareness) as the best fit model and provide initial indices of validity and internal consistency reliability for the newly titled Multicultural Counseling Knowledge and Awareness Scale. Este artículo informa los resultados de 2 estudios diseñados para probar y revisar la Escala de Conciencia de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
327
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 239 publications
(345 citation statements)
references
References 50 publications
14
327
2
2
Order By: Relevance
“…Bandura (1997) (Constantine & Ladany, 2001;Sue, 2001;Sue et al, 1982;Sue et al, 1992); (b) models of multicultural counseling (D'Andrea & Daniels, 2001;Fuertes & Gretchen, 2001;Ponterotto et al, 2000); (c) assessment of multicultural counseling competence (Coleman, 1996;D'Andrea et al, 1991;LaFromboise et al, 1991;Ponterotto et al, 2002;Sodowsky et al, 1994;Worthington, Mobley, Franks, & Tan, 2000); and (d) training of multicultural competencies (Abreu et al, 2000;Constantine, 2001a;Constantine & Ladany, 2000;Constantine, Ladany, Inman, & Ponterotto, 1996;Ponterotto & Casas, 1987;Quintana & Bernal, 1995). In addition to the progress made in theory and assessment, a recent survey indicated that 73% of APA-accredited counseling psychology programs offered one or more multicultural courses, and 42% of them required a multicultural course (Quintana & Bernal, 1995).…”
Section: General Cse Measures: Why They Are Not Sufficient For Multicmentioning
confidence: 99%
See 4 more Smart Citations
“…Bandura (1997) (Constantine & Ladany, 2001;Sue, 2001;Sue et al, 1982;Sue et al, 1992); (b) models of multicultural counseling (D'Andrea & Daniels, 2001;Fuertes & Gretchen, 2001;Ponterotto et al, 2000); (c) assessment of multicultural counseling competence (Coleman, 1996;D'Andrea et al, 1991;LaFromboise et al, 1991;Ponterotto et al, 2002;Sodowsky et al, 1994;Worthington, Mobley, Franks, & Tan, 2000); and (d) training of multicultural competencies (Abreu et al, 2000;Constantine, 2001a;Constantine & Ladany, 2000;Constantine, Ladany, Inman, & Ponterotto, 1996;Ponterotto & Casas, 1987;Quintana & Bernal, 1995). In addition to the progress made in theory and assessment, a recent survey indicated that 73% of APA-accredited counseling psychology programs offered one or more multicultural courses, and 42% of them required a multicultural course (Quintana & Bernal, 1995).…”
Section: General Cse Measures: Why They Are Not Sufficient For Multicmentioning
confidence: 99%
“…The Multicultural Counseling Knowledge and Awareness Scale (MCKAS), formerly titled the Multicultural Counseling Awareness Scale (MCAS; Ponterotto et al, 1996), was revised to assess the knowledge and awareness components of multicultural counseling competence (Ponterotto et al, 2002). Originally, Ponterotto, Sanchez, and Magids (1991) attempted to develop the MCAS to measure the Sue et al tripartite model (awareness, knowledge, and skills).…”
Section: General Cse Measures: Why They Are Not Sufficient For Multicmentioning
confidence: 99%
See 3 more Smart Citations